Risk Analysis Of Chili Chili Farming In The Koli Transmigration Settlement Unit, Oba Sub-District, Tidore City Islands, North Maluku Province - A. Marsaoly, Hasrul; Ekaria, Ekaria (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
The agricultural pattern for residents in the Transmigration Settlement area or known as trans koli already uses modern technology that produces maximum production. Cayenne pepper production risk is a loss to farmers caused by the emergence of a production process that cannot be handled. The purpose of this study was to analyze the costs, income and income of cayenne pepper farming and to analyze production risk, cost risk and risk of cayenne pepper farming income in the Koli Transmigration Settlement Unit, Oba District, Tidore City, North Maluku Islands Province. The analytical method used in this research is descriptive quantitative analysis to analyze farming and risk analysis. The results of this study are that the average total production costs incurred by farmers in the Trans Koli area during one planting season is IDR 1,464,198 and the average total income during one harvest season is IDR 4,062,293 and the average chili farming income earned farmer. for one harvest season IDR 2,599,094. This explains that the income of the respondent farmers in producing cayenne pepper is greater than the total production costs incurred by the cost risk with a coefficient of variation of 6.40, this is due to the high transportation costs. While the results of the lowest risk level with a coefficient of variation of 1.26. This is because of the selling price relative and stable production is indicated by a lower level of production risk with a coefficient of variation of 1.60 compared to cost risk.